Motivation and productivity of employees in higher education during the first lockdown - Jacqueline R. Rietveld; Djoerd Hiemstra; Aleid Brouwer; Jan Waalkens (Administrative Sciences, 2022)
In a cross-sectional study among 623 employees of a higher education institution, we examined the relations between perceived competence, autonomy, relatedness, intrinsic motivation, and productivity during the first lockdown in the spring of 2020. The results indicate that, relative to the period before the lockdown, the employees experienced an increase in autonomy and competence, but a decrease in relatedness, intrinsic motivation, and productivity. Structural equation modelling revealed that the decrease in productivity can be explained by a decrease in intrinsic motivation, which in turn can be explained by changes in relatedness, autonomy, and perceived competence. Thus, during the lockdown, both positive and negative motivational consequences of teleworking were observed. However, the ultimate consequence for employees' productivity was negative. An important difference between this study and previous studies on the topic of teleworking, is that the present examined the motivational process under extreme circumstances in which employees had to switch overnight form onsite to remote working.
Keywords: 350; motivation; productivity; remote work